Novel Insights Into Gas Embolism in Sea Turtles: First Description in Three New Species - Crespo-Picazo, Jose L.; Parga, Mariluz; Bernaldo de Quirós, Yara; Monteiro, Danielle; Marco-Cabedo, Vicente; Llopis-Belenguer, Cristina; García-Párraga, Daniel (Frontiers in Marine Science, 2020)
The recent finding of gas embolism and decompression sickness in loggerhead sea turtles (Caretta caretta) in the Mediterranean Sea challenged the conventional understanding of marine vertebrate diving physiology. Additionally, it brought to light a previously unknown source of mortality associated with fisheries bycatch for this vulnerable species. In this paper, we use ultrasonography to describe gas embolism in a leatherback sea turtle (Dermochelys coriacea), a green sea turtle (Chelonia mydas) and an olive ridley sea turtle (Lepidochelys olivacea) from accidental capture in a gillnet, bottom trawl and pair-bottom trawl respectively. This is the first description of this condition in these three species worldwide. These cases of gas embolism suggest that this may be a threat faced by all sea turtle species globally.